Enhancing the effectiveness of smoking treatment research: conceptual bases and progress. (19th November 2015) - Baker, Timothy B.; Collins, Linda M.; Mermelstein, Robin; Piper, Megan E.; Schlam, Tanya R.; Cook, Jessica W.; Bolt, Daniel M.; Smith, Stevens S.; Jorenby, Douglas E.; Fraser, David; Loh, Wei‐Yin; Theobald, Wendy E.; et al.
Abstract: Background and aims: A chronic care strategy could potentially enhance the reach and effectiveness of smoking treatment by providing effective interventions for all smokers, including those who are initially unwilling to quit. This paper describes the conceptual bases of a National Cancer Institute‐funded research program designed to develop an optimized, comprehensive, chronic care smoking treatment. Methods: This research is grounded in three methodological approaches: (1) the Phase‐Based Model, which guides the selection of intervention components to be experimentally evaluated for the different phases of smoking treatment (motivation, preparation, cessation, and maintenance); (2) the Multiphase Optimization Strategy (MOST), which guides the screening of intervention components via efficient experimental designs and, ultimately, the assembly of promising components into an optimized treatment package; and (3) pragmatic research methods, such as electronic health record recruitment, that facilitate the efficient translation of research findings into clinical practice. Using this foundation and working in primary care clinics, we conducted three factorial experiments (reported in three accompanying papers) to screen 15 motivation, preparation, cessation and maintenance phase intervention components for possible inclusion in a chronic care smoking treatment program. Results: This research identified intervention components with relatively strong evidence of effectiveness at particular phases of smoking treatment and it demonstrated the efficiency of the MOST approach in terms both of the number of intervention components tested and of the richness of the information yielded. Conclusions: A new, synthesized research approach efficiently evaluates multiple intervention components to identify promising components for every phase of smoking treatment. Many intervention components interact with one another, supporting the use of factorial experiments in smoking treatment development.